Study on the Flexural Strength of Polyester Composite Beams and Coconut Husk Charcoal Powder - nusyirwan nusyirwan; Hayatul Fikri (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2026)
Polymer materials are being rapidly researched because they have the potential to replace metal materials, offering advantages such as low mass, ease of shaping, and moisture resistance. However, this material still has many disadvantages, including low mechanical strength and easy cracking under impact. Unsaturated polyester is a widely used matrix material for composite materials in the engineering field, such as for vehicle bodies and ship hulls. In this study, the flexural strength of polyester composites reinforced by coconut shell charcoal was studied. From flexural strength testing according to ASTM D 390-92, a tendency to increase flexural strength with the addition of a coconut shell charcoal mixture from 10% to 20% was observed; beyond 20%, the flexural stress decreased. The maximum flexural stress value obtained at a percentage of 20% coconut shell charcoal was 132.43 N/mm². This value can increase the maximum flexural stress of pure polyester, which was only 52.10 N/mm², by 253.35%